Do you say uh or uhm? A cross-linguistic approach to filler particle use in heritage and majority speakers across three languages - Böttcher, Marlene; Zellers, Margaret (Frontiers in Psychology, 2024)
Filler particles like uhm in English or ähm in German show subtle language-specific differences and their variation in form is related to socio-linguistic variables like gender. The use of fillers in a second language has been shown to differ from monolinguals' filler particle use in both frequency and form in different language contexts. This study investigates the language-specific use of filler particles by bilingual heritage speakers in both their languages, looking at the dominant majority language in the society and their minority heritage language spoken at home. This is done based on heritage Russian and German data and majority German and English data from the RUEG corpus. Language-specific fillers were extracted from the corpus and analysed for their occurrence and segmental form. The frequency analysis suggests an influence of bilingualism, age group and formality of the situation on the filler frequency across all languages. The number of filler particles is higher in formal, older and bilingual speech. This is discussed related to cognitive load which is higher in formal situations, older speakers and in bilingual speech planning, and also discussed to speech style which differs between situations and social groups. The form analysis reveals an effect of gender across all languages and contact situations. The vocalic-nasal filler particles (e.g. uhm) are more frequently found in female German and English and in bilingual Russian. This is discussed related to language specific filler particles and the socio-linguistic aspect of filler particle use. The results from this study suggest language-specific filler use in both languages of heritage speakers, while also revealing societal filler usage conventions related to gender which is also produced by heritage speakers.